Silo bag storage - Bartosik, Ricardo Enrique (2024)
Silo bags are a flexible, hermetic storage system made of polyethylene; they are available in a variety of sizes and can be used to store grains and their byproducts. Silo bags have gained extensive adoption as a hermetic storage solution in Argentina. Annually, this method is employed for the storage of roughly 50 million tonnes (Mt) of grain across various levels, including farms, grain elevators, industries, and even port facilities. Moreover, silo bags have gained recognition as a viable storage alternative in over 50 countries globally, ranging from cold climates like Canada and Russia to tropical regions such as Brazil and Colombia. In addition to the plastic bags themselves, the silo bag system involves other essential components, including bagging and extracting machines, as well as grain carts. These pieces of equipment have been specially designed with a high working capacity, enabling them to handle impressive volumes of 300–400 t per hour. Furthermore, silo bag monitoring systems have been developed based on CO2 concentration measurements and airtightness evaluations through a pressure decay test. In general, when dry grain is stored in silo bags, the CO2 levels range from 1% to 3%, while the O2 levels range from 18% to 16%. As the moisture content (MC) and temperature of the grain increase, the modification of the interstitial atmosphere becomes more pronounced, resulting in CO2 concentrations of up to 30% and O2 levels of 5% to 0% for moist grain. Few instances of insect presence in silo bags have been reported, with data analysis indicating that unfavorable environmental conditions hinder insect development. Nevertheless, suitable pest control strategies, based on phosphine fumigation and controlled atmospheres, have been successfully implemented. The quality of grains stored in silo bags is influenced by the interaction between MC and temperature. When the MC is sufficiently low to inhibit microbiological activity, the temperature itself has minimal impact, allowing for storage even during the summer without deterioration in quality. When the MC is sufficiently high to permit microbial activity, the deterioration of quality parameters during winter is mitigated by the synergistic of low temperature and the modified atmosphere. However, in spring and summer heightened microbial activity and other detrimental processes intensify, resulting in a decline in quality parameters that cannot be compensated for by the modified atmosphere alone.